2004
DOI: 10.1088/0964-1726/14/1/010
|View full text |Cite
|
Sign up to set email alerts
|

Performance modeling of a piezohydraulic actuation system with active valves

Abstract: Piezohydraulic actuation is the use of hydraulic fluid to rectify the high frequency, small stroke oscillation movement of the piezoceramic stack into a unidirectional movement at a specific combination of stroke and force. In recent years, piezohydraulic pumps have been studied and developed by several groups. This paper presents two steady flow models based on different approximations of the hydraulic fluid. In the first model we assume a fully developed incompressible viscous flow, and in the second model w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 9 publications
0
44
0
1
Order By: Relevance
“…This configuration allows only a unidirectional valve opening. When the fluid flows into the chamber from the inlet valve, the outlet valve port does not allow any fluid to come into the chamber and vice versa [9]. In this research, 0.05mm, 0.08mm, and 0.15mm thicknesses of reed valve were considered for the performance experiment.…”
Section: Configuration Of the Whole Systemmentioning
confidence: 99%
“…This configuration allows only a unidirectional valve opening. When the fluid flows into the chamber from the inlet valve, the outlet valve port does not allow any fluid to come into the chamber and vice versa [9]. In this research, 0.05mm, 0.08mm, and 0.15mm thicknesses of reed valve were considered for the performance experiment.…”
Section: Configuration Of the Whole Systemmentioning
confidence: 99%
“…The output velocity from the numerical analysis increased with the actuating frequency, and the velocity decreased after 35 Hz similar to the experimental results according to the flow loss because the working fluid velocity could not follow the acceleration of the piezo pump. The decrease of the operating velocity at the high frequency has been explained as due to the slow response time of the working fluid inside the chamber [11], and to the irregular flow inside the pipe [12,13]. Chaudhuri [1] concluded that the flow velocity decreased due to the fluid compression in the limited space at the high frequency.…”
Section: Analysis Of Internal Flow Distribution By Pump Frequencymentioning
confidence: 99%
“…Thanks to the development of linear drive technology, researchers can explore many related can achieve very high reciprocating motion frequency and cooperate with active or passive rectification valves to provide fluid power to the actuation system [15][16][17]. The requirements of bidirectional drive and high rectification efficiency make the active valves preferred alternatives [18,19]. The valves need to be controlled in coordination with the pumping cylinder based on the sensing of the cylinder motion.…”
Section: Introductionmentioning
confidence: 99%